Inventarisasi Mamalia di Hutan Harapan Sumatera Selatan - Boby Hariadi; Wilson Novarino; - Rizaldi (Universitas Andalas, 2012)
An inventory of mamalian species in restoration forest at The Harapan Rainforest, South Sumatra was conducted from March to June 2012. The animals were photograped using camera traps, personal encounters as well as indirect observations through foot prints, scratches, excavations, feces, and calls. This study has documented 23 species of mammals which belong to 15 families and 7 orders. From a total of 412 identified photograps, it was known that wild boars (Sus scrofa) were the most frequently photographed (89 images) while leopard (Prinailurus bengalensis) and Marbled cat (Pardofelis marmorata) were only photograped once for each species. We described each species by comparing to some references and discussed their implications for conservation.Keywords: mamalian species, camera traps, forest restoration